2018
DOI: 10.1016/j.stem.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening Enhances Kidney Organoid Differentiation from Human Pluripotent Stem Cells and Enables Automated Multidimensional Phenotyping

Abstract: Organoids derived from human pluripotent stem cells are a potentially powerful tool for high-throughput screening (HTS), but the complexity of organoid cultures poses a significant challenge for miniaturization and automation. Here, we present a fully automated, HTS-compatible platform for enhanced differentiation and phenotyping of human kidney organoids. The entire 21-day protocol, from plating to differentiation to analysis, can be performed automatically by liquid-handling robots, or alternatively by manua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
391
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 375 publications
(433 citation statements)
references
References 50 publications
19
391
0
2
Order By: Relevance
“…This is not the first report of the automated generation of human pluripotent stem cell derived kidney structures. Czerniecki et al 24 previously reported the use of a Tecan liquid handling platform for the distribution of undifferentiated hPSCs prior to differentiation and the automated image capture of nephron features across a 96-well format. The approach described here has several points of difference from that the previous study, including the protocol for directed differentiation and the increased histological complexity of the resulting tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the first report of the automated generation of human pluripotent stem cell derived kidney structures. Czerniecki et al 24 previously reported the use of a Tecan liquid handling platform for the distribution of undifferentiated hPSCs prior to differentiation and the automated image capture of nephron features across a 96-well format. The approach described here has several points of difference from that the previous study, including the protocol for directed differentiation and the increased histological complexity of the resulting tissue.…”
Section: Discussionmentioning
confidence: 99%
“…To model the G1 variants within a kidney context, we differentiated the G1 and G0 lines into kidney organoids using an adherent culture protocol we have previously established ( Figure 1B) [5][6][7]13,14 . Both G0 and G1 iPSC lines differentiated into kidney organoids without major structural differences, expressing markers of nephron structure including PODXL in glomerular epithelial cells, LTL in the proximal tubule, and E-cadherin in the distal tubule, in appropriately patterned and contiguous segments ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Using CRISPR-Cas9 mediated genome editing, we engineered iPSCs homozygous for the G1 risk allele and differentiated these cells into threedimensional kidney organoids. To evaluate cell-type specific effects of the APOL1 high-risk genotype, we also performed single-cell RNA-sequencing (scRNA-seq), which we and others have previously leveraged to uncover novel biology of how cell-specific phenotypes contribute to kidney development or disease in organoids and other models [10][11][12][13][14] . Here we present the application of genome-edited iPSC-derived kidney organoids and single-cell transcriptomics to profile APOL1-mediated effects on kidney organoids relevant to disease processes.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput in vitro assays provide a platform to screen for therapeutic pharmacological 53 or biological agents 54,55 prior to cumbersome pre-clinical in vivo models. We performed endothelial tubule formation, under serum starvation, as a functional readout to assesses whether EV+ or EV-CM elicit provascular functions in a suboptimal microenvironment.…”
Section: The Secretome Of Panc-msc Demonstrated Vascular and Tissue Rmentioning
confidence: 99%